ChemInform Abstract: Oxidative Dimerization of Silylallenes via Activation of the Allenic C(sp2)—H Bond Catalyzed by Copper(I) Chloride and N‐Hydroxyphthalimide. Issue 7 (January 2016) - Sabbasani, Venkata R.; Lee, Daesung
Abstract: An efficient procedure is elaborated for the oxidative dimerization of silylallenes (I), (III), and (V).